Regulasi dan Perkembangannya dalam Sektor Publik - Muhammad Arifin; Yogi Aryo Pratomo; Nurtia Rahmadani (Jurnal Bisnis Inovatif dan Digital, 2025)
The research discusses the evolution of public sector regulation in Indonesia, from the pre-reform era to the contemporary reform era, and the implementation challenges encountered. The library research method is adopted to facilitate an exploration of different regulatory mechanisms and paradigms that influence national financial governance. The research shows a trend towards the establishment of more accountable and transparent systems of regulation. Major challenges identified are the absence of skilled human resources, underdeveloped information technology infrastructures, and limited awareness of public accountability.